2019
DOI: 10.1063/1.5121230
|View full text |Cite
|
Sign up to set email alerts
|

An integrable all-silicon slotted photonic crystal Raman laser

Abstract: The design of an integrable all-silicon Raman laser of a foot print of ∼7 μm is proposed based on a slotted photonic crystal nanocavity. The slot has been considered to be made of a silicon nanocrystal to encash its giant Raman gain coefficient, along with the tight spatial and temporal confinement of light in the slot, exhibiting a lasing efficiency of ∼17.8% at a wavelength of 1552 nm. Simulations depict that the device requires a very small optical threshold power of the order of 0.5 μW. Tolerances to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, due to the indirect bandgap material property of silicon, efficient lasers cannot be made directly on silicon. Although some efforts have been made by resorting to nanostructures [8][9][10], erbium doping [11][12][13], and Raman effects [14,15], there is still a long way for real-world applications. A viable method for silicon light sources is the integration of external III-V materials with silicon photonics.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the indirect bandgap material property of silicon, efficient lasers cannot be made directly on silicon. Although some efforts have been made by resorting to nanostructures [8][9][10], erbium doping [11][12][13], and Raman effects [14,15], there is still a long way for real-world applications. A viable method for silicon light sources is the integration of external III-V materials with silicon photonics.…”
Section: Introductionmentioning
confidence: 99%
“…In reference [113], Pradhan et al reported the design of an integrable all-silicon Raman laser of a foot print of 7µm, based on a slotted photonic crystal nanocavity, which takes advantage the giant Raman gain coefficient of a silicon nanocrystal [56]. The device exhibits a lasing efficiency of 18% at a wavelength of 1552 nm, with an optical threshold power of the order of 0.5 µW.…”
Section: Raman Laser In Nanophotonicsmentioning
confidence: 99%
“…Nevertheless, these limitations can be removed by further intensifying the SRS interaction using the slow‐light phenomenon inside a silicon nanocrystal embedded slotted photonic crystal waveguide (SPCW), which has been demonstrated by the authors in [17, 18]. SPCWs are potential waveguide geometries which offer ultra‐high optical confinement [19] and, thereby, explore myriad of electro‐optical and all‐optical functionalities reported recently [2024]. Silicon nanocrystal embedded in silica host (Sinc/SiO2), on the other hand, is a promising material in the silicon photonics platform, which offers substantial enrichment of the optical non‐linearities, especially the SRS gain coefficient, which is enhanced by four orders of magnitude in the near‐ to mid‐infrared spectral region [2529].…”
Section: Introductionmentioning
confidence: 99%